Pengembangan UMKM Olahan Pangan Lokal Dalam Gerakan One Day No Rice (ODNR) Di Kota Depok - Purnawan, Endar; Nogroho, Fentiny (Jurnal Ilmu Kesejahteraan Sosial, 2016)
This thesis reveals the development of micro, small and medium local food entreprise. Furthermore, this descriptive research uses a qualitative approach. The result of this research show that ODNR action has encouraged the appearance of UMKM in a culinary sector and it also provided local food – non rice and non wheat. The roles of UMKM in a ODNR action is producing, supplying, distributing, marketing local food, conducting inovation, socializing ODNR action, creating new UMKM and job vacancies. Things supporting the development of UMKM are place, equipment, capital, human resources, skills, raw materials, and ODNR action itself. On the other hand, there are some factor that inhibit its development, such as the alteration of human resources and setting of working time, lack of creativity, lack of knowledge and scarcity of raw materials.